Natal dispersal driven by environmental conditions interacting across the annual cycle of a migratory songbird - Studds, Colin E. (National Academy of Sciences, 2008)
Natal dispersal, the process through which immature individuals permanently depart their natal area in search of new sites, is integral to the ecology and evolution of animals. Insights about the underlying causes of natal dispersal arise mainly from research on species whose short dispersal distances or restricted distributions make them relatively easy to track. However, for small migratory animals, the causes of natal dispersal remain poorly understood because individuals are nearly impossible to track by using conventional mark–recapture approaches. Using stable-hydrogen isotope ratios in feathers of American redstarts (Setophaga ruticilla) captured as immature birds and again as adults, we show that habitat use during the first tropical nonbreeding season appears to interact with latitudinal gradients in spring phenology on the temperate breeding grounds to influence the distance traveled on the initial spring migration and the direction of natal dispersal. In contrast, adult redstarts showed considerable site fidelity between breeding seasons, indicating that environmental conditions did not affect dispersal patterns after the first breeding attempt. Our findings suggest that habitat occupancy during the first nonbreeding season helps determine the latitude at which this species of Neotropical–Nearctic migratory bird breeds throughout its life and emphasize the need to understand how events throughout the annual cycle interact to shape fundamental biological processes.